Causal role of immune cells on risk of Parkinson’s disease: a Mendelian randomization study - Gu, Jian; Qiao, Yue; Cong, Shuyan (Frontiers in Aging Neuroscience, 2024)
Background: Previous observational studies have suggested a correlation between immune cells and Parkinson's Disease (PD), yet specific investigations into the causal relationship between the two remain limited. This study aims to explore this potential causal relationship.We utilized genome-wide association study (GWAS) data on immune cells and Parkinson's Disease, conducting a two-sample Mendelian randomization (MR) analysis using single nucleotide polymorphisms (SNPs). To estimate causality, we employed Inverse Variance Weighting (IVW), MR-Egger, and Weighted Median (WM) methods. For sensitivity analysis, we used Cochran's Q test, MR-Egger intercept, leave-one-out analysis, and funnel plots.Results: After False Discovery Rate (FDR) correction, the effects of PD on immune cells, and vice versa, were not statistically significant. These include CX3CR1 on CD14+ CD16-monocyte (OR = 0.91, 95% CI = 0.86 -0.96, p=0.0003 pFDR = 0.152), CD62L-CD86+ myeloid DC AC (OR = 0.93, 95% CI = 0.89 -0.97, p=0.0005, pFDR = 0.152),CD11b on Mo (OR = 1.08, 95% CI = 1.03 -1.13, p=0.001, pFDR = 0.152), CD38 on igd+ cd24-(OR = 1.14, 95% CI = 1.06 -1.23, p=0.001, pFDR = 0.152), D14+ cd16+ monocyte%monocyte (OR = 1.10, 95% CI = 1.04 -1.17, p=0.001, pFDR = 0.159). Additionally, PD may be causally related to the immune phenotype of CM CD8br %T cell (beta = 0.10, 95% CI = 1.14-1.16, p=0.0004, pFDR = 0.151), SSC-A on monocyte (beta = 0.11, 95% CI = 1.15 -1.18, p=0.0004, pFDR = 0.1SsC-A on monocyte). No pleiotropy was determined.Disease through the MR method, which could provide a new direction for the mechanistic research and clinical treatment of PD.